(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Hemochromatosis is a genetic disorder characterized by excessive iron absorption and deposition in vital organs, leading to chronic complications such as liver cirrhosis, diabetes, cardiomyopathy, and arthritis. Although common in Western populations, especially those of Northern European descent, the condition is considered rare in Central Asia, including Uzbekistan. This article explores the current knowledge on the prevalence of hemochromatosis in Uzbekistan, the challenges in diagnosis, and what steps are being taken within the healthcare system to address this condition.